Subchronic toxicity test of black garlic (Allium sativum) ethanol extract in liver histology of female mice (Mus musculus) - Huwaidah, Jihan Farhah; Agustina, Eva; Purnamasari, Risa (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
Black garlic is an innovative product from garlic which contains S-allyl cysteine (SAC), flavonoids, and polyphenols during the aging process. The use of black garlic as a medicine has not been studied regarding its toxicity to the liver, so research is needed regarding the safety of its use through toxicity tests. The purpose of this study was to determine the effect of giving various doses of black garlic ethanol extract on liver histology and to determine the safe dosage of black garlic ethanol extract for consumption. The method used was the treatment of black garlic ethanol extract in the treatment group at doses of 5, 50, 100, 300, 600, 1000, and 2000 mg/kg BW orally in mice to determine the effect on the histology of the mice's liver. The results showed that the greater the treatment dose of black garlic ethanol extract, the greater the percentage of damage to hepatocyte cells in the form of necrosis in the histology of the mice liver. The highest percentage of damaged cells experiencing necrosis was 49% at a dose of 2000 mg/kg BW. The use of doses that are safe for consumption has not been found in this study due to cell damage found > 30% in the category of moderate damage. So further testing is needed using a lower dose or by administering the extract over a shorter period of time to determine the safe dose for consumption.